Content-Based Image Retrieval for Multi-Class Volumetric Radiology Images: A Benchmark Study - Farnaz Khun Jush; Steffen Vogler; Tuan Truong; Matthias Lenga (IEEE Access)
With the growing number of images generated daily in radiological practices and the digitization of historical studies, we face large databases where metadata can be incomplete or incorrect. Content-based image retrieval (CBIR) can help to manage these datasets by efficiently locating and retrieving relevant information by only using image data as a query. Recent studies have shown the potential use of pre-trained vision embeddings for CBIR in the context of radiology image retrieval for specific tasks like single-organ retrieval or distinguishing between normal and abnormal tissues. However, a comprehensive benchmark for the retrieval of 3D volumetric medical images is still lacking. In this study, we establish a benchmark for multi-class volumetric retrieval for different retrieval modes. The retrieval modes are defined based on end-point use-cases, which include Full-Scan Retrieval, Targeted-Region Retrieval, and Precise-Localization Retrieval. We utilize the TotalSegmentator dataset, comprising 104 detailed anatomical structures, to evaluate the performance of embeddings derived from pre-trained models across the proposed retrieval modes. We show the potential of CBIR for organ retrieval by achieving a retrieval recall of 1.0 for diverse anatomical regions with a wide size range. The methodology presented in this paper utilizes publicly available image data and embedding models without requiring any task-specific fine-tuning. This benchmark aims to enable further development and allow for a more consistent evaluation of CBIR approaches in the context of 3D medical imaging.